(untitled) (Dhaka University Journal of Science, 2016)
One of the major problems with Electrical Impedance Tomography (EIT) is the lack of spatial sensitivity within the measured volume. In this paper, sensitivity distribution of the tetrapolar impedance measurement system was visualized considering a cylindrical phantom consisting of homogeneous and inhomogeneous medium. Previously, sensitivity distribution was analysed analytically only for the homogeneous medium considering simple geometries and the distribution was found to be complex1,2. However, for the inhomogeneous volume conductors sensitivity analysis needs to be done using finite element method (FEM). In this paper, the results of sensitivity analysis based on finite element method using COMSOL Multiphysics simulation software are presented. A cylindrical non-uniform, inhomogeneous phantom, which mimics the human upper arm, was chosen to do the experiments by varying different parameters of interest. A successful method for controlling the region of interest was found where the sensitivity was maximum. Refining the finite element mesh size and introducing multifrequency input current (up to 1 MHz) this simulation method can be further improved. Dhaka Univ. J. Sci. 64(1): 7-13, 2016 (January)